Sistem Pendukung Keputusan Pemilihan Sales Supervisor Menerapkan Metode EDAS berdasarkan Pembobotan ROC - Purnama, Iwan; Zulkifli, Zulkifli; Nasution, Muhammad Bobbi Kurniawan; Karim, Abdul; Trianovie, Sri (Building of Informatics, Technology and Science (BITS), 2023)
Sales is a job that aims to sell a product in the form of goods, services and others and provide the best service to consumers or buyers. Sales will work optimally if managed properly. The person who works to manage sales work is a sales supervisor. Sales Supervisor is someone who is responsible for managing the work procedures of each sales person under his control. A supervisor is required to be able to control every task implementation of a salesperson. If the company hires someone who is not qualified to be a sales supervisor, it will cause losses. So to determine the sales supervisor, a system is needed that will help select good and quality sales supervisor candidates according to the criteria set by the company. The right system to assist companies in making elections is SPK. Decision support system (DSS) is a system that is deliberately created to assist certain parties in making decisions with quality and objective results. SPK requires a method. In this study the method used is the EDAS method. The EDAS method has a function, namely to produce a ranking value by implementing mathematical formulations correctly according to the rules. The mathematical formulation is systematically arranged by experts and produces a ranking value which will eventually be assembled into an accurate decision. From the results of this study, a value of 0.5348 was obtained by Mandala as an alternative to B7, which is the best sales supervisor candidate